2002
DOI: 10.1080/165019702760279233
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Stimulation (Acupuncture) for the Treatment of Idiopathic Anterior Knee Pain

Abstract: A randomized controlled study was conducted to evaluate the effect of acupuncture treatment in idiopathic anterior knee pain, a pain syndrome without known aetiology. Fifty-eight patients, clinically and radiologically examined, were randomly assigned to either deep or minimal superficial acupuncture treatment. The patients were treated twice weekly for a total of 15 treatments. The main outcome measurements were one leg vertical jump, functional score, daily VAS recording and skin temperature. Fifty-seven pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
16

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 26 publications
2
39
0
16
Order By: Relevance
“…Naslund and colleagues 30 compared the effect of deep versus superficial needling (which they considered to be placebo) in a group of 58 individuals with idiopathic anterior knee pain. The authors found no statistical difference between the 2 methods.…”
Section: Deep Versus Superficial Needlingmentioning
confidence: 99%
“…Naslund and colleagues 30 compared the effect of deep versus superficial needling (which they considered to be placebo) in a group of 58 individuals with idiopathic anterior knee pain. The authors found no statistical difference between the 2 methods.…”
Section: Deep Versus Superficial Needlingmentioning
confidence: 99%
“…108 This would suggest that there is a difference between experimental and clinical pain and probably between different pain states.…”
mentioning
confidence: 99%
“…5 Fifty eight patients, clinically and radiologically examined, were randomly assigned to either deep or minimal superficial acupuncture treatment. The patients were treated twice weekly for a total of 15 treatments.…”
mentioning
confidence: 99%